Optical frequency divider with division uncertainty at the 10−21 level. Issue 4 (26th September 2016) - Yao, Yuan; Jiang, Yanyi; Yu, Hongfu; Bi, Zhiyi; Ma, Longsheng
Abstract: Optical clocks with unprecedented accuracy of 10 −18 promise innovations in many research areas. Their applications rely to a large extent on the ability of precisely converting the frequency from one optical clock to another, or particularly to the frequencies in the fiber telecom band for long-distance transmission. This report demonstrates a low-noise, high-precision optical frequency divider, which realizes accurate optical frequency conversion and enables precise measurement of optical frequency ratios. By measuring against the frequency ratio between the fundamental and the second harmonic of a 1064-nm laser instead of a second copy of the same system, we demonstrate that the optical frequency divider has a fractional frequency division instability of 6 × 10 −19 at 1 s and a fractional frequency division uncertainty of 1.4 × 10 −21 . The remarkable numbers can support frequency division of the best optical clocks in the world without frequency-conversion-caused degradation of their performance.